Significance of forms and foci of metacognitive regulation in collaborative science learning of less and more successful outcome groups in diverse contexts - Iiskala Tuike; Volet Simone; Jones Cheryl; Koretsky Milo; Vauras Marja (SPRINGER, 2022)
This study investigated how metacognitive regulation (MR), especially its forms and foci, was manifested in less and more successful outcome groups' collaborative science learning in diverse learning contexts. Whilst previous research has shown that different forms and foci of MR exist in collaborative learning, their role in groups' learning outcomes remains unexplored. Drawing conclusions from different studies has been difficult because these have used different conceptualisations and analytic methods. In the present study, the learning processes of less and more successful outcome groups from three diverse collaborative science learning contexts were scrutinised. The contexts differed in academic level, disciplinary subject, and national culture. The same theory-based conceptualisations, coding systems, coders, and analyses were used across contexts. In addition, the tasks studied were designed using the same guiding principles. Transcribed video and audio recordings of the groups' verbal interactions for two distinct interaction segments from these tasks formed the basis of the analyses. Manifestation of forms and foci of MR were quantitatively and qualitatively illustrated in each context. The main findings show that the manifestation of MR of less and more successful outcome groups demonstrated similarities and differences in the three different learning contexts. This study contributes to a contextualised understanding of MR in collaborative science learning, and highlights the importance of using similar, rigorous analytical tools across diverse contexts.